2017
DOI: 10.1509/jm.15.0178
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Traditional Advertising and Social Messages on Brand-Building Metrics and Customer Acquisition

Abstract: This study examines the relative effectiveness of traditional advertising, impressions generated through firm-toconsumer (F2C) messages on Facebook, and the volume and valence of consumer-to-consumer (C2C) messages on Twitter and web forums for brand-building and customer acquisition efforts. The authors apply vector autoregressive modeling to a unique data set from a European telecom firm. This modeling approach allows them to consider the interrelations among traditional advertising, F2C impressions, and vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
87
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(96 citation statements)
references
References 57 publications
1
87
0
8
Order By: Relevance
“…One possible explanation is that, like, share, and comment are three engagement behaviors with different levels of involvement [7]. While brand posts' linguistic characteristics can impact all of the three engagement behaviors, their effects are not large enough to greatly change highly-involving engagement behaviors (i.e., share, comment).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One possible explanation is that, like, share, and comment are three engagement behaviors with different levels of involvement [7]. While brand posts' linguistic characteristics can impact all of the three engagement behaviors, their effects are not large enough to greatly change highly-involving engagement behaviors (i.e., share, comment).…”
Section: Discussionmentioning
confidence: 99%
“…To digital marketers, enhancing consumer engagement with brand posts on social media is both vital and challenging [2][3][4]. Consumer engagement with brand posts is positively related with: brand awareness, preference, and consideration [5][6][7][8]; brand equity [5,9]; and brand performance (e.g., sales, new customer acquisition, brand value, etc.) [2,7,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This particular opinion was formed due to concerns that advertising might have no effect on sales. But, since [10,30,43,14,23] confirmed that advertising has a positive influence on sales, all suspicions on the effectiveness of these models and its application in decision making were dismissed. Naturally, significant effort was put into developing models that could optimize the allocation of an advertising budget, which is also the task of this paper.…”
Section: Advertisement Placement Problemmentioning
confidence: 99%
“…For marketers, consumer engagement with brand posts is crucial because it is essential for creating social contagion effects, whereby a brand's message reaches non-subscribers or those not participating in a conversation with the brand [4]. Research has also shown that consumer engagement with brand posts is positively related with: brand awareness, preference, and consideration [3,[5][6][7]; brand equity [8]; and brand performance (e.g., sales, new customer acquisition, value, etc.) [3,7,9].…”
Section: Introductionmentioning
confidence: 99%